El género en la concepción y aplicación de la justicia penal - Miró Quesada Gayoso, Josefina (2022)
The article analyzes, from a legal and criminological perspective, the role of gender in the conception and application of the criminal justice system, throughout its different stages. As such, it starts by questioning the apparent neutrality offered by criminal law categories, built up and interpreted from an androcentric lens that excludes and devalues female experiences, interests and values.Through a critical literature review that studies the interaction of punitive and patriarchal power, the direct and indirect empirical effects, at a comparative level, of criminal laws, substantive and procedural, designed and applied without a gender perspective are exposed and analyzed. The author afifirms that legal practitioners that apply criminal law tools ought to do so in consideration with gender sensitivity, while formulas of alternative justice that decentralize the traditional punitive paradigm are devised.